Phaleria macrocarpa Flavonoid as a Potent MMP-1 Inhibitor for Endometriosis Therapy: In silico Study - Maharani; Sutrisno (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Endometriosis is a gynaecological disorder in women and causes infertility. Several therapeutic were developed to reduce endometriosis cases, one of them was matrix metalloproteinase (MMP) inhibitor. This study investigated the potential activity of the flavonoids in Phaleria macrocarpa fruit as MMP1 inhibitors for endometriosis. Methods: In silico modelling was used in this study. Six flavonoid structures were retrieved from PubChem NCBI database. A targeted protein, MMP1 was taken out from Protein Data Bank with ID 1CGE and predicted the active sites. Six flavonoids and MMP1 was interacted by molecular docking using Molegro virtual Docker version 5 and analyzed using PyMol 2.2 and Discovery Studio version 21.1.1. Three-dimensional complex structure of flavonoids – MMP1 showed interaction in the same active sites and performed an amino acid residue Glu219 as catalytic site. Results: Six flavonoids of Phaleria macrocarpa were divided into two patterns and generated varied binding energy. Glycitin and Catechin 7-O-beta-D-xyloside showed low score of binding energy and depicted similar structure with four aromatic rings. 8-Prenylnaringenin performed lower binding energy than naringenin, eriodictyol, and 5-O-methylgenistein. Conclusion: In silico analysis suggested that six flavonoids compounds is potent as MMP1 inhibitor and might be interfered endometriosis pathophysiology. In vivo and in vivo investigations are required for further analysis.